OPTIMIZATION OF INTELLECTUAL CAPITAL TO REALIZE EMOTIONAL INTELLIGENCE THROUGH ORGANIZATIONAL STRESSORS - Dwiarta, I Made Bagus; Suharyanto, Suharyanto; Widhayani, Puri Setioningtyas; Asj’ari, Fachrudy (Universitas Brawijaya, Indonesia, 2022)
This research is important for the achievement of the college plan because at PGRI University Adi Buana Surabaya is also developing student cooperatives and employee cooperatives so that business sustainability occurs that can educate employees and students to get to know cooperatives and entrepreneurship. This study aims to test the influence of intellectual capital on emotional intelligence through organizational stressors as an intervening variable for cooperative actors in Surabaya. This study analyzes how intellectual capital plays a role in optimizing organizational stressors and emotional intelligence and how organizational stressors play a role in optimizing the emotional intelligence of cooperative actors in Surabaya. Some variables are analyzed as factors that affect emotional intelligence, namely intellectual capital and organizational stressors. This study is a type of explanatory study, reviewed from its analytical approach and classified into quantitative methods. The population of this study is all cooperative actors in Surabaya, and the sample is determined based on accidental techniques. Sampling in this study used Ferdinand's formula with the number of samples used as many as 156 people. The data was collected through questionnaires and analyzed using SEM (semantic equation modeling). This research is useful for the development of human resource management science. This study showed that intellectual capital has a significant and positive effect on organizational stressors, and intellectual capital has a significant and positive effect on emotional intelligence. In contrast, organizational stressors have insignificant and negative effects on emotional intelligence. The Cooperative is expected to solve or fix the cooperative actors' organizational stressors to solve the cooperative actor's problems.